Identifying Good Practice in National Adaptation Plans: A Global Review - Shammugam, Shivenes; Reckien, Diana; Grafakos, Stelios; Bockarjova, Marija; Choi, Hyeryung; Salvia, Monica; Viero, Giulia; Pietrapertosa, Filomena; Lionggo, Indriany (Global Green Growth Institute, 2024)
This report presents a global analysis of the contents of National Adaptation Plans (NAPs) documents submitted to the Secretariat of the United Nations Framework Convention on Climate Change (UNFCCC) before the 1st of January 2024. The present report has two main objectives: to present the results of the global review of NAPs derived from a review framework that was developed as part of this works and to highlight and share good practices on NAP thematic areas from countries, for other countries to learn from to either creating a NAP or to refine their existing NAP. Director of the CGIAR Climate Impact Platform, Aditi Mukherji, was a developer of the NAP-GP Framework.